3D printed dielectric ceramic without a sintering stage. Issue 1 (December 2018) - Väätäjä, Maria; Kähäri, Hanna; Ohenoja, Katja; Sobocinski, Maciej; Juuti, Jari; Jantunen, Heli
Abstract This paper presents for the first time the fabrication of dielectric ceramic parts by 3D printing without sintering. The printable paste was prepared by mixing a carefully selected amount of water-soluble Li2 MoO4 powder with water. A viscous mixture of solid ceramic particles and saturated aqueous phase was formed with a solid content of 60.0 vol.%. Printing of the sample discs was conducted with material extrusion using a low-cost syringe-style 3D printer. The consolidation and densification of the printed parts occurred during both printing and drying of the paste due to extrusion pressure, capillary forces, and recrystallization of the dissolved Li2 MoO4 . Complete drying of the paste was ensured by heating at 120 °C. The microstructure showed no delamination of the printed layers. Relatively high densities and good dielectric properties were obtained, especially when considering that no sintering and only pressure from the extrusion was employed. This approach is expected to be feasible for similar ceramics and ceramic composites.